KONSEP PENDIDIK DAN METODE PEMBELAJARAN YANG HUMANIS MENURUT IBNU KHALDUN - Kiki Sumber Rejeki (Mozaic : Islam Nusantara, 2020)
This study aims to find out and analyze the concept of educators and humanist learning methods according to Ibn Khaldun in his book entitled "Muqaddimah". The concept of educators and methods of learning in question is the behavior of educators in providing teaching to learners. The meaning of humanist according to Ibn Khaldun is a teaching that contains elements of humanity according to his nature as a human being. The approach used in this research is qualitative descriptive by reviewing the book of Muqaddimah with publisher of Maktabah Al-Hidayah as primary source and translation book of Muqaddimah with publisher Pustaka Al-Kautsar as secondary source and other supporting book. This research produces some educational concepts and learning methods that are humanist according to Ibn Khaldun.